The Effect of Administration of Longan (DimocarpusLonganL Steud)Leaf Extract Cream on Collagen Density and MMP-1 Expression in the Dermis of BALB/C Mice Exposed to UV-B Rays - Ruri Eka Maryam Mulyaningsih (Universitas Sultan Agung Semarang, 2020)
INTRODUCTION: UV-B exposure to the skin may produce ROS, decreasing collagen density and increasing MMP-1 expression. Longan leaf extract cream contains antioxidant and is expected to prevent decrease in collagen density and MMP-1 expression increase.